2020
DOI: 10.1016/j.jembe.2020.151444
|View full text |Cite
|
Sign up to set email alerts
|

Response of a natural Antarctic phytoplankton assemblage to changes in temperature and salinity

Abstract: Take-down policy If you believe that this document breaches copyright please contact us providing details, and we will remove access to the work immediately and investigate your claim.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 108 publications
2
9
0
Order By: Relevance
“…During the summer months (December-March), meltwaters on the Western Antarctic Peninsula, where this study was undertaken, occur regularly. It has been shown that meltwater transports high particle loads to the coastal water thereby reducing incident light conditions and salinity that affect microbial community dynamics, leading to changes in species composition (Schloss et al, 2008;Antoni et al, 2020). In this study, we showed different proportions of fungal sequences between different water types.…”
Section: Discussionsupporting
confidence: 55%
“…During the summer months (December-March), meltwaters on the Western Antarctic Peninsula, where this study was undertaken, occur regularly. It has been shown that meltwater transports high particle loads to the coastal water thereby reducing incident light conditions and salinity that affect microbial community dynamics, leading to changes in species composition (Schloss et al, 2008;Antoni et al, 2020). In this study, we showed different proportions of fungal sequences between different water types.…”
Section: Discussionsupporting
confidence: 55%
“…Recently, significant changes in physical conditions such as increasing summer temperatures in the atmosphere and surrounding waters were observed in the southwestern Ross Sea continental shelf and lengthening of the free ice season was found in Ross Sea polynya induced by climate change ( Stammerjohn et al, 2008 ; Comiso et al, 2011 ; Schine et al, 2016 ; Kaufman et al, 2017 ). These climate-induced stressors can lead to changes in the size structure and assemblage composition of phytoplankton and physiological shifts in the phytoplankton communities ( Yun et al, 2019 ; Antoni et al, 2020 ; Hernando et al, 2020 ). Moreover, herbivores encounter rapidly changing food quality in company with changes in the diverse species, quantity, and biochemical characteristics of their prey ( Scott, 1980 ; Finkel et al, 2010 ).…”
Section: Discussionmentioning
confidence: 99%
“…In this manner, productivity shows a positive correlation with the increase in temperature up to species optimum (Huertas et al, 2011). Changes in species composition are already being observed in response to altered temperature patterns (Larsson et al, 2015;Hernando et al, 2015Hernando et al, , 2020Antoni et al, 2020), considering that the ability to adapt to such changes are species-specific in a phytoplankton assemblage (Gao et al, 2012). Consequently, the pronounced variability in oceanatmosphere exchanges of heat along WAP has a strong impact on primary production, community composition and ecosystem functioning (Ducklow et al, 2013;Meredith et al, 2017;Hernando et al, 2015).…”
Section: Introductionmentioning
confidence: 92%
“…Overall, organisms' responses to heat waves may involve reversible adjustment of their physiology by changing the content of some biomolecules or with activation of antioxidant systems, among other processes (Hernando et al, 2015;Hernando et al, 2018;Hernando et al, 2020;de la Rosa et al, 2020). Because phytoplankton growth and composition are highly dependent on environmental conditions (Galloway and Winder, 2015;Antoni et al, 2020), there is an urgent need to understand how microalgae will be affected at the biochemical level in our warming world. Also, algae inhabiting regions at different latitudes are adapted to different ranges of temperatures.…”
Section: Introductionmentioning
confidence: 99%